DIMENSI POLITIK DAN SOSIAL PEMANASAN GLOBAL - Hadi, Sudharto P. (Jurnal Legislasi Indonesia, 2009)
The impact of global warming has been around us. The impactincludes sea level rise, sea temperature rise, air temperaturerise, increase rainfall, increase evaporation and increase tropicalstorm. Indonesia is vulnarable to the impact of global warmingdue to the fact that Indonesia is an archipelagic country withmany small islands, has second longest coast line in the world,and has 65 % of population live in coastal area. The availabilityof water is influenced by climate change and it will affect toagriculture, animal husbandry and fishery.Heavy and unregular rainfall, thunderstorm and heattemperature creating flood, landslide are among the phenomenaof climate change triggered by global warming. The commitmentto reduce CO2 emmission has been declared through ProtocolKyoto in 1997. However, the realization went slowly. Japanhas a commitment to reduce its emmission up to 6% but itsproduction of emmision still 8.1%. European countries targetedto reduce its emmission up to 8%. Until the year of 2003, theyreduced its emmission at 1.7%. The U.S, the largest producer ofCO2 emmission, has not ratified Protocol Kyoto.After world conference on climate change in Bali, Indonesiafollowed up by setting up a National Action Plan and promotingmitigation and adaptation strategies. The issues regarding thisstrategies are the weakness of coordination among relateddepartment, sectoral egoism and big project orientation. Anotherstrategy called energy efficiency is required to promote. Thisstrategy includes the change of behaviour to safe the energy, touse public transportation, to utilize renewable energy, to plantthe tree etc. If the environmentally friendly movement is widelydone by many people across the country, the contribution toreduce the impact of climate change could be significant.